A road infrastructure asset management process: gains in efficiency and effectiveness. Issue 1 (25th May 2018) - Adey, Bryan T
Abstract : There are a large number of efforts around the world to obtain more net benefits from road infrastructure assets. This can be seen through the proliferation of codes and guidelines and the increasing amount of research in road infrastructure asset management. Many of these codes and guidelines and much of the research, however, are focused on only part of the large complex problem of road infrastructure asset management. In efforts to improve the efficiency and effectiveness of the process, however, it is likely that it is useful to define clearly the entire road infrastructure management process. In this paper, this is done at a high level. It is hoped that using this high-level process as a starting point will help ensure that further efforts to increase the efficiency and effectiveness of road infrastructure asset management are successful not only in general, but also in particular through the exploitation of computer systems. The process can be used as a starting point by road infrastructure asset managers as they establish their own more detailed process, in which all involved stakeholders agree as to the activities involved in the management of road infrastructure assets and the reasons why.